2008
DOI: 10.1556/abiol.59.2008.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the applicability of molecular markers linked to the PVY extreme resistance geneRysto, and the identification of new markers

Abstract: In this study molecular markers linked to the Rysto gene, which originates from the wild potato species Solanum stoloniferum and confers extreme resistance against PVY, were identified and the applicability of recently published Rysto, markers was analyzed. Three RAPD markers covering a total distance of 8.60 cM were detected in this experiment. The closest of these markers was located 0.53 cM from the gene. From among the published markers only one had diagnostic value in the experimental plant material, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 13 publications
2
21
0
Order By: Relevance
“…Valkonen et al (2008) found that the markers linked to the Ry sto gene (previously identified by Flis et al 2005 andSong et al 2005) are suitable for the selection of potato genotypes carrying the Ry sto gene from independent accession of S. stoloniferum; however, in our experiments, the markers mentioned above-with one exception-have not proved suitable for selection. These markers could not be detected in our experimental plant material, or they proved to be monomorphic (Cernák et al 2008). Only the STM0003-111 marker reported by Song et al (2005) could be detected in these plants.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Valkonen et al (2008) found that the markers linked to the Ry sto gene (previously identified by Flis et al 2005 andSong et al 2005) are suitable for the selection of potato genotypes carrying the Ry sto gene from independent accession of S. stoloniferum; however, in our experiments, the markers mentioned above-with one exception-have not proved suitable for selection. These markers could not be detected in our experimental plant material, or they proved to be monomorphic (Cernák et al 2008). Only the STM0003-111 marker reported by Song et al (2005) could be detected in these plants.…”
Section: Discussionmentioning
confidence: 58%
“…According to our previous results, the female parent, White Lady, carries the Ry sto gene in simplex form (Cernák et al 2008).…”
Section: Plant Materialsmentioning
confidence: 80%
See 1 more Smart Citation
“…It is also possible to tag specific genes related to environmental factors that could have useful applications, for example in molecular ecology. This is because IT uses primers based on allele sequences of functionally characterized genes, and thus specific banding patterns corresponding to plant phenotypes can be identified [103,104]. However, development of such markers depends on the availability of genomic databases with several target sequences for IT markers.…”
Section: Gene-targeted and Functional Markers (Gtms And Fms)mentioning
confidence: 99%
“…Examples of MAS have been published with regard to Ry adg and/or Ry sto (Dalla Rizza et al 2006; Gebhardt et al 2006;Valkonen et al 2008; Ottoman et al 2009). Markers linked to Ry adg (Kasai et al 2000) and Ry sto (Cernák et al 2008) have been optimised and validated in diverse genetic backgrounds. However, there are some additional PVY-resistant potato cultivars that are of interest to breeders, but for which the underlying genes remain elusive.…”
Section: Introductionmentioning
confidence: 99%